Salam Betawi Punya Aye: Brand Awareness Development Strategy For Visitors of KPB Betawi Setu Babakan - Aprilia, Lu’luwatin Rosdiana; Putra, Bagus Alifiano; Chofifah, Marthika Nour (Gondang: Jurnal Seni dan Budaya, 2024)
This study explores strategies for developing visitor brand awareness through the use of "Salam Betawi Punya Aye" in the Betawi Cultural Village area of Setu Babakan. The SWOT (Strengths, Weaknesses, Opportunities, Threats), IFAS (Internal Factors Analysis Summary), and EFAS (External Factors Analysis Summary) analysis methods were employed to formulate appropriate strategies. Findings indicate the significant potential of "Salam Betawi Punya Aye" in enhancing brand awareness, yet it faces challenges such as lengthy duration and lack of financial support. Proposed strategies include capitalizing on opportunities such as promoting Betawi culture in the education and tourism sectors and leveraging technology. In conclusion, the primary focus should be on addressing weaknesses, such as shortening the duration of the greeting and increasing flexibility. This, it is hoped that these strategies will effectively strengthen the promotion and preservation of Betawi culture in Setu Babakan.